Lawsuit Against the Regent of Deli Serdang Regarding the Appointment of an Interim Village Head in Buah Nabar Village from a Fiqh Siyasah Perspective (Analytical Study of Ptun Number 42/G/2021/Ptun. Medan) - Simorangkir, Suhrawardi; Tarigan, Tetty Marlina (IHSA Institute, 2025)
This study aims to analyze the verdict of the Medan Administrative Court (PTUN Medan) Decision Number 42/G/2021/PTUN.MDN regarding the lawsuit against the Regent of Deli Serdang concerning the interim appointment of a village head in Buah Nabar Village, Sibolangit Sub-district, Karo Regency, which resulted in certain parties feeling disadvantaged. Additionally, this study seeks to analyze the fiqh siyasah (Islamic political jurisprudence) perspective on the decision of PTUN Medan Number 42/G/2021/PTUN.MDN regarding the lawsuit filed against the regent for the interim appointment of a village head. This research is normative in nature, employing qualitative normative analysis. It involves a document study approach using various secondary data sources such as legislation, legal norms, and court decisions